Myrmecotypus haddadi sp. nov.—a new species of ant resembling sac spider from the Bolivian orocline (Araneae: Corinnidae: Castianeirinae) - Perger, Robert; Rubio, Gonzalo D. (Zootaxa, 2021)
A new species of ant resembling sac spider of the subfamily Castianeirinae, Myrmecotypus haddadi sp. nov. is described from the Sub-Andean area at the Bolivian orocline. The species was collected from low herbaceous vegetation along the edges of the Chiquitano and Cerradao forest.